The Effectiveness of Health Promotion Models with Comic Media, Videos, and Lectures on Helminthiasis to Medical Faculty Students at Universitas Prima Indonesia - Ali Napiah Nasution; Lia Christiana; Intan Audrey Alicia Hutabarat; Christina J. R. Esmaralda Lumbantobing (Jurnal Penelitian Pendidikan IPA, 2023)
The research aims to assess the knowledge about worm infections among students at the Faculty of Medicine, Prima Indonesia University, through health promotion media. The methodology involves the Sample T test Pretest and Posttest method, with a sample size of 154, determined based on prior research outcomes. The data analysis utilizes SPSS 25. The findings of the study indicate that the mean knowledge score prior to educational intervention via media was 36.3506, with a standard deviation of 3.32653. After the intervention, the mean knowledge score rose to 50.4416, accompanied by a standard deviation of 3.63891. This indicates an improvement in student knowledge scores before and after the health education intervention, utilizing video lectures and comics as media. The pretest and posttest outcomes exhibit an increase from 77.50% to 119.35% after the media intervention.